The effectiveness of contrast bath to reduce joint pain in the elderly - Rusminingsih, Esri; Agustina, Nur Wulan; Wulan, Dyah Ayu Nawang (Universitas Muhammadiyah Purwokerto, 2019)
Background: The aging process results in changes in the musculoskeletal system causing a decrease in function of joints, loss of elasticity and limited mobility. This condition also causes joint pain, especially in the joints supporting the body weight, namely the knee. The previous studies discussed the method of reducing pain using a contras bath which was implemented by soaking parts of the body that experience pain alternately with hot and cold water, this was difficult to apply if the pain occurs in the upper body. Modifications in contrast baths using compresses to the knee joint have never been implemented before.Objective: This study aimed to figure out the effect of the contras bath method using compresses to reduce knee joint pain in the elderly.Method: The design of this study was pre-experimental with one group of pretest-posttest. The sample used was 16 elderly who were selected by random sampling at Posyandu (a center for pre- and postnatal health care and information for elderly) in village of Sawit Gantiwarno, Klaten. Contrast bath is applied by giving compresses of warm and cold water alternately with a ratio of three minutes: one minute per-day during 20 minutes, for a week. Pain measurement is performed using the Visual Analog Scale (VAS) instrument.Result: The mean of knee pain before giving a contrast bath was 5.44, whereas after a contrast bath was 3.50. Bivariate analysis used Wilcoxon, it showed p value <0.05 which means there was a significant difference in knee joint pain before and after contrast baths were applied.Conclusion: Administration of contrast bath can reduce knee joint pain in the elderly.